Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Câu 3:
a) \(\dfrac{12}{36}=\dfrac{12:12}{36:12}=\dfrac{1}{3}\)
\(\dfrac{-16}{20}=\dfrac{-16:4}{20:4}=\dfrac{-4}{5}\)
b) \(\dfrac{21}{105}=\dfrac{21:21}{105:21}=\dfrac{1}{5}\)
\(\dfrac{35}{150}=\dfrac{35:5}{150:5}=\dfrac{7}{30}\)
Câu 4:
a) \(\dfrac{3}{10}+\dfrac{5}{10}=\dfrac{3+5}{10}=\dfrac{8}{10}=\dfrac{4}{5}\)
b) Ta có: \(\left(-27\right)\cdot36+64\cdot\left(-27\right)+23\cdot\left(-100\right)\)
\(=\left(-27\right)\cdot\left(64+36\right)+23\cdot\left(-100\right)\)
\(=-27\cdot100-23\cdot100\)
\(=100\left(-27-23\right)\)
\(=-50\cdot100=-5000\)
c) \(\dfrac{5}{8}+\dfrac{3}{12}=\dfrac{15}{24}+\dfrac{6}{24}=\dfrac{21}{24}=\dfrac{7}{8}\)
d) Ta có: \(\dfrac{-2}{17}+\dfrac{3}{19}+\dfrac{-15}{17}+\dfrac{16}{19}+\dfrac{5}{6}\)
\(=\left(-\dfrac{2}{17}+\dfrac{-15}{17}\right)+\left(\dfrac{3}{19}+\dfrac{16}{19}\right)+\dfrac{5}{6}\)
\(=-1+1+\dfrac{5}{6}\)
\(=\dfrac{5}{6}\)
\(B=\frac{3+\frac{8}{12}+\frac{9}{13}-\frac{12}{17}}{4+\frac{8}{12}+\frac{12}{13}-\frac{16}{17}}+\frac{4+\frac{16}{60}-\frac{24}{213}-\frac{32}{11}}{5+\frac{20}{61}-\frac{36}{213}-\frac{40}{11}}\)
\(\Leftrightarrow B=\frac{3\left(1+\frac{8}{12}+\frac{3}{13}-\frac{4}{17}\right)}{4\left(1+\frac{8}{12}+\frac{3}{13}-\frac{4}{17}\right)}+\frac{4\left(1+\frac{4}{60}-\frac{6}{213}-\frac{8}{11}\right)}{5\left(1+\frac{4}{60}+\frac{6}{213}-\frac{8}{11}\right)}\)
\(\Leftrightarrow B=\frac{3}{4}+\frac{4}{5}\)
\(\Leftrightarrow B=\frac{15}{20}+\frac{16}{20}\)
\(\Leftrightarrow B=\frac{31}{20}\)
Bài 1:
a: \(x=\dfrac{2}{3}:\dfrac{3}{5}=\dfrac{2}{3}\cdot\dfrac{5}{3}=\dfrac{10}{9}\)
b: \(x=\dfrac{17}{8}:\dfrac{7}{17}=\dfrac{17}{8}\cdot\dfrac{17}{7}=\dfrac{289}{56}\)
c: \(x=-\dfrac{3}{4}:\dfrac{7}{12}=\dfrac{-3}{4}\cdot\dfrac{12}{7}=\dfrac{-63}{28}=-\dfrac{9}{4}\)
d: \(\Leftrightarrow x\cdot\dfrac{1}{6}=\dfrac{3}{8}-\dfrac{1}{4}=\dfrac{1}{4}\)
hay \(x=\dfrac{1}{4}:\dfrac{1}{6}=\dfrac{3}{2}\)
e: \(\Leftrightarrow\dfrac{1}{2}:x=-4-\dfrac{1}{3}=-\dfrac{17}{3}\)
hay \(x=-\dfrac{1}{2}:\dfrac{17}{3}=\dfrac{-3}{34}\)
Bài 1:
a; \(\dfrac{5}{18}\) + \(\dfrac{8}{19}\) - \(\dfrac{7}{21}\) + (- \(\dfrac{10}{36}\) + \(\dfrac{11}{19}\) + \(\dfrac{1}{3}\)) - \(\dfrac{5}{8}\)
= \(\dfrac{5}{18}\) + \(\dfrac{8}{19}\) - \(\dfrac{1}{3}\) -\(\dfrac{10}{36}\) + \(\dfrac{11}{19}\) + \(\dfrac{1}{3}\) - \(\dfrac{5}{8}\)
= (\(\dfrac{5}{18}\) - \(\dfrac{10}{36}\)) + (\(\dfrac{8}{19}\) + \(\dfrac{11}{19}\)) - (\(\dfrac{1}{3}\) - \(\dfrac{1}{3}\)) - \(\dfrac{5}{8}\)
= (\(\dfrac{5}{18}\) - \(\dfrac{5}{18}\)) + \(\dfrac{19}{19}\) - 0 - \(\dfrac{5}{8}\)
= 0 + 1 - \(\dfrac{5}{8}\)
= \(\dfrac{3}{8}\)
b; \(\dfrac{1}{13}\) + (\(\dfrac{-5}{18}\) - \(\dfrac{1}{13}\) + \(\dfrac{12}{17}\)) - (\(\dfrac{12}{17}\) - \(\dfrac{5}{18}\) + \(\dfrac{7}{5}\))
= \(\dfrac{1}{13}\) - \(\dfrac{5}{18}\) - \(\dfrac{1}{13}\) + \(\dfrac{12}{17}\) - \(\dfrac{12}{17}\) + \(\dfrac{5}{18}\) - \(\dfrac{7}{5}\)
= (\(\dfrac{1}{13}\) - \(\dfrac{1}{13}\)) + (\(\dfrac{12}{17}\) - \(\dfrac{12}{17}\)) + (-\(\dfrac{5}{18}\) + \(\dfrac{5}{18}\)) - \(\dfrac{7}{5}\)
= 0 + 0 + 0 - \(\dfrac{7}{5}\)
= - \(\dfrac{7}{5}\)
Bài 1 c;
\(\dfrac{15}{14}\) - (\(\dfrac{17}{23}\) - \(\dfrac{80}{87}\) + \(\dfrac{5}{4}\)) + (\(\dfrac{17}{23}\) - \(\dfrac{15}{14}\) + \(\dfrac{1}{4}\))
= \(\dfrac{15}{14}\) - \(\dfrac{17}{23}\) + \(\dfrac{80}{87}\) - \(\dfrac{5}{4}\) + \(\dfrac{17}{23}\) - \(\dfrac{15}{14}\) + \(\dfrac{1}{4}\)
= (\(\dfrac{15}{14}-\dfrac{15}{14}\)) + (\(-\dfrac{17}{23}+\dfrac{17}{23}\)) - (\(\dfrac{5}{4}\) - \(\dfrac{1}{4}\)) + \(\dfrac{80}{87}\)
= 0 + 0 - 1 + \(\dfrac{80}{87}\)
= - \(\dfrac{7}{87}\)
Bài 1:
a: =25+75=100
b: =60-17-43+12=12
c: =-2-18=-20
d: =-3+36-17=36-20=16
Bài 2:
a: =-102
b: =-1000
c: =12x15=180
d: =21x(-10)=-210
\(\dfrac{3}{17}\) .\(\dfrac{6}{29}\) - \(\dfrac{3}{17}\).\(\dfrac{35}{29}\) + 2022\(\dfrac{3}{17}\)
= (\(\dfrac{3}{17}\).\(\dfrac{6}{29}\) - \(\dfrac{3}{17}\).\(\dfrac{35}{29}\)) + 2022 + \(\dfrac{3}{17}\)
= \(\dfrac{3}{17}\).(\(\dfrac{6}{29}\) - \(\dfrac{35}{29}\)) + 2022 + \(\dfrac{3}{17}\)
= \(\dfrac{3}{17}\).(-1) + 2022 + \(\dfrac{3}{17}\)
= (- \(\dfrac{3}{17}\) + \(\dfrac{3}{17}\)) + 2022
= 0 + 2022
= 2022
b; \(\dfrac{5}{6}\) - (\(\dfrac{1}{3}\) + \(\dfrac{1}{2}\)).20%
= \(\dfrac{5}{6}\) - \(\dfrac{5}{6}\).\(\dfrac{1}{5}\)
= \(\dfrac{5}{6}-\dfrac{1}{6}\)
= \(\dfrac{4}{6}\)
= \(\dfrac{2}{3}\)
= -3/12 :3 +17/36 = -1/4 . 1/3 +17/36 = -1/12 +17/36= -3/36 + 17/36 = 14/36 =7/18
a) (x.7 + 8) : 5 = 10
x.7 + 8 = 10.5
x.7 + 8 = 50
x.7 = 50 - 8
x.7 = 42
x = 42 : 7
x = 6
b) (x + 5).19 : 13 = 57
(x + 5).19 = 57 . 13
(x + 5).19 = 741
x + 5 = 741 : 19
x + 5 = 39
x = 39 - 5
x = 34
c) 4.(36 - 4.x) = 64
36 - 4x = 64 : 4
36 - 4x = 16
4x = 36 - 16
4x = 20
x = 20 : 4
x = 5
d) 7,6 : 19 . x = 3,2
0,4 . x = 3,2
x = 3,2 : 0,4
x = 8
e) (x : 2 + 50) : 5 = 12
x : 2 + 50 = 12 . 5
x : 2 + 50 = 60
x : 2 = 60 - 50
x : 2 = 10
x = 10 . 2
x = 20
g) 280 : (17 + 3.x) = 4
17 + 3x = 280 : 4
17 + 3x = 70
3x = 70 - 17
3x = 53
x = 53/3
h) 6.(28 - 8.x) = 72
28 - 8x = 72 : 6
28 - 8x = 12
8x = 28 - 12
8x = 16
x = 16 : 8
x = 2
i) (x - 15) : 3 : 12 = 6
(x - 15) : 3 = 6 . 12
(x - 15) : 3 = 72
x - 15 = 72 . 3
x - 15 = 216
x = 216 + 15
x = 231
36-12:4×3+17
=36 - 9 + 17
= 44
k cho mik nha